Kekuatan Mengikat Pertimbangan Hukum Putusan Mahkamah Konsitusi dalam Perkara Pengujian Undang-Undang (Studi Putusan Nomor 20/PUU-XIX/2021) - Gunawan A. Tauda (Fakultas Hukum Universitas Islam Indonesia, 2024)
The Constitutional Court has the authority to determine the addressed subject in order to make adjustments to laws that have been assessed or interpreted for their constitutionality. This determination usually only applies to applications that are granted and not applications that are rejected in their entirety. In Decision Number 20/PUU-XIX/2021 (Case for Reviewing Article 50 paragraph (4) of Law Number 14 of 2005 on Teachers and Lecturers in conformity with the 1945 Constitution), the Court emphasized in the Legal Considerations section two facts that were proven to be sufficiently justified in accordance with the law, which then became the basis for the Court to instruct the addressed subject to be adjusted. The issue to be addressed in this study is, do the legal considerations (Court Opinion) in the decision have the similar legally binding force as the decisive ruling. This is a normative legal research, accompanied by the use of a statutory approach, a case approach, and a conceptual approach. The results of the study indicate that based on the implementation of Decision Number 20/PUU-XIX/2021, legal reasoning, both ratio decidendi and obiter dicta, have the same legally binding force as the ruling. Legal considerations in a decision can be a